PENGARUH KOMUNIKASI “WORD OF MOUTH” TERHADAP MINAT BELI KONSUMEN PRODUK MS GLOW - Pratama, Dimas Surya; M, Deddy Satria (SOURCE : Jurnal Ilmu Komunikasi, 2023)
At this time the competition among beauty product companies vying with each other to attract consumer buying interest. Very tight competition forces every company to be able to implement a good marketing strategy that is customer oriented so that it can win the market. Word of mouth or word of mouth communication is considered quite effective in influencing potential customers. Word of mouth has more competitive advantages and ease in conveying information. This study aims to examine the effect of word of mouth communication on consumer purchase interests for MS Glow products. The object of this research is MS Glow product. This study uses the S-O-R (Stimulus-Organism-Response) theory. The population of this study were all students of Communication Studies at University of Malikussaleh. The sample in this study amounted to 90 people. Sampling using Non-probability Sampling, namely by Purposive Sampling. The data collection instrument used a questionnaire with a Likert scale, each of which had been tested and met the validity and reliability requirements. Data analysis used simple linear regression and the regression equation in this study was ???? = 21.239 + 0.505???? with a significant value of 0.000 which is less than 0.05. So it can be concluded that there is an influence of word of mouth communication on the intention to buy MS Glow products in Communication Studies students at University of Malikussaleh with an R2 value of 31.7% while the remaining 68.3% is influenced by other factors not examined in this study.